Elections in Cape Verde, 1991-2016: testing the second-order election model in a consolidated semi-presidential African democracy - Santana Pereira, J. (2020)
In this article, we analyse patterns of turnout and electoral choices of Cape Verde’s citizens in different types of elections, looking at all legislative, presidential and local elections held between 1991 and 2016, and testing four hypotheses derived from the second-order election model about differences in terms of turnout, number of spoiled/blank papers, results for the incumbent party and the electoral success of smaller parties. Our results show that, in what regards turnout and electoral behaviour, local elections present the features of second-order elections much more clearly than the presidential elections in this semi-presidential regime. However, this pattern does not necessarily mean that voters look at the latter as less second-order, but since they often took place in the honeymoon period of the legislative electoral cycle, it may only mean that there were lower incentives to punish the incumbent and/or disengage from political participation.